Solar photocatalytic degradation of 4-chlorophenol: Mechanism and kinetic modelling - Abeish, Abdulbasit M.; Ang, Ha Ming; Znad, Hussein (Taylor & Francis Ltd., 2013)
The present study reports a mechanism and kinetic model of solar photocatalytic degradation of 4-chlorophenol (4-CP) and its intermediates based on the experimental results. Three intermediate compounds hydroquinone (HQ), 4-chlorocatechol (4cCat) and phenol were found during the solar degradation of different 4-CP concentrations using 0.5 g/L TiO2 as a photocatalyst. In order to obtain more details about the photocatalytic reaction pathway and the kinetic model, set of experiments were carried out using the major intermediates (HQ and 4cCat) as model reactants. To minimise the number of variables and give more accuracy to the kinetic model, the adsorption constants of 4-CPand its intermediates were obtained experimentally. The reaction mechanism for the photocatalytic degradation of 4-CP is proposed. The proposed model predicts well the concentrations of 4-CP and its by-products during the solar photocatalytic degradation at different initial concentrations. The model provides a very good fit of the experimental data and works for a wide range of 4-CP initial concentrations (25–100 mg/L).